ANALISIS PENERAPAN TA’ZIR PADA PEMBIAYAAN MURABAHAH DI BPR SYARIAH MADINAH LAMONGAN
The process of transferring or distributing the fund to the customers, or what so called as the outlay needs such a definite contract to apply in the process of job capital budgeting. In BPR Syariah Madinah Lamongan, the contract applied is the contract of mura>bah